2011
DOI: 10.1007/s10517-011-1211-5
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Taxotere Chemotherapy for Metastatic Tumor Pleurisy in Cats with Spontaneous Breast Cancer

Abstract: Systemic and intrapleural chemotherapy for metastatic tumor pleurisy was carried out in cats with breast carcinoma. The animals (n=18) were divided into 2 groups. Cats of the systemic chemotherapy group received 3-6 courses of taxotere (30 mg/m(2); n=7) or 3 courses of taxotere (20 mg/m(2)) in combination with doxorubicin (20 mg/m(2)at 21-day intervals (n=5) during the adjuvant period of therapy for metastatic tumor pleurisy. Objective effect was attained in 10 (84.6%) cats: partial remission in 3 (25%) and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 6 publications
0
10
1
Order By: Relevance
“…To date, the only published article in cats dealing with IC gave a median survival time of 15 days in six cats presented with a diagnosis of pleural carcinomatosis of mammary origin and treated with cyclophosphamide. 18 In this same report, only 20% of cats survived at least 1 month after treatment, and none survived as long as 1.5 months. 18 Consequently, the results of our study are similar to those previously reported, with a mean survival time of 9.6 days and a median survival time of 8 days, and 0% of cats were alive 1 month after initiation of treatment.…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…To date, the only published article in cats dealing with IC gave a median survival time of 15 days in six cats presented with a diagnosis of pleural carcinomatosis of mammary origin and treated with cyclophosphamide. 18 In this same report, only 20% of cats survived at least 1 month after treatment, and none survived as long as 1.5 months. 18 Consequently, the results of our study are similar to those previously reported, with a mean survival time of 9.6 days and a median survival time of 8 days, and 0% of cats were alive 1 month after initiation of treatment.…”
Section: Discussionmentioning
confidence: 84%
“…18 In this same report, only 20% of cats survived at least 1 month after treatment, and none survived as long as 1.5 months. 18 Consequently, the results of our study are similar to those previously reported, with a mean survival time of 9.6 days and a median survival time of 8 days, and 0% of cats were alive 1 month after initiation of treatment. In human oncology, presence of malignant effusion is usually associated with a median survival that does not exceed 6–12 months, despite multiple treatment options.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations